Die Veränderungen der landwirtschaftlichen Betriebsgrößenstruktur durch die Agrarreform in Chile - Bähr, Jürgen; Fischbock, Antje (ERDKUNDE, 1987)
This study investigates the effects of the agrarian reform begun in Chile in 1965 on the structure of farm sizes by comparing the agricultural censuses of 1964/65 with those of 1975/76. Farm area, area under agricultural use, arable land and area under irrigation were each used as reference values. It was demonstrated that: (i) traditional large scale land ownership had been abolished, (ii) medium-sized farms had been strengthened and now presented the most important element in Chilean agriculture, (iii) the recently formed small farms were not viable, and (iv) the situation of the minifundistas had not been improved. In the long term increasing sales of land by owners of small enterprises may lead to the renewed formation of large-scale farm ownership, though it will be distincdy different to the traditional latifundium on the basis of its capital-intensive production form.